Rare Earth Oxide-Doped Fullerene and Titania Composites and Photocatalytic Properties of Methylene Blue Under Visible Light - Meng1, Ze-Da; Chen1, Ming-Liang; Zhang1, Feng-Jun; Zhu1, Lei; Choi1, Jong-Geun; Oh1, Won-Chun (Asian Journal of Chemistry, 2011)
Rare-earth oxide-doped fullerene and TiO2 composites (Y-fullerene/TiO2) were prepared by a sol-gel method. The composite obtained was characterized by BET surface area measurements, X-ray diffraction, transmission electron microscopy and energy dispersive X-ray analysis. A methylene blue solution under visible light irradiation was used to determine their photocatalytic activity. Excellent photocatalytic degradation of methylene blue solution was observed using the Y-fullerene/TiO2 composite under visible light.